Impact of dielectric properties on ionic conductivity of Ce0.9Sm0.1O1.95 via defect interaction - Sk. Anirban (Elsevier, 2021)
This study mainly investigates the defect interaction mediated ionic conductivity of Ce0.9Sm0.1O1.95. The ionic conductivity mainly depends on the concentration of free oxygen vacancies. The formed oxygen vacancies are bounded with dopant cations due to columbic interaction which depends on the dielectric constant of the material. With the rise in temperature dielectric constant increases and dopant–vacancy association decreases. Consequently, ionic conductivity increases with temperature due to the enhancement of concentration of free oxygen vacancies. The association and migration energy decrease at higher temperature.